Exploring the Application of Digital Nostalgia System in Dementia Care from the Perspective of Narrative Gerontology - Fan, Kuang-Yi; Wu, Pei-Fen (Advances in Social Sciences Research Journal, 2024)
In recent years, modern medical technology has advanced significantly, increasing the average lifespan of Taiwanese individuals. However, dementia, a common disease among the elderly, has also become more prevalent. The cognitive decline caused by dementia can severely impact the physical, mental, and spiritual health of patients. This study aimed to explore the impact of using digital nostalgia technology to provide cognitive stimulation for patients with dementia, specifically through the use of the "Recall" system developed by our research team. We analyzed the narrative context of patients and employed a pre-test and post-test experimental design, inviting five mild dementia patients to participate. The research methodology mainly involved qualitative research, and we conducted semi-structured interviews with patients using nostalgic photos, divided into four topics: personal background description, most memorable experiences, specific themes, and personal photo sharing. We used NVivo qualitative analysis software to analyze the interview transcripts by coding and classifying the nodes to explore the differences in the patient’s narrative context before and after the intervention. This study found that patients participating in the digital experimental activities were more eager to share their old photos. These stimulated memories and led to good subjectivity, continuity, coherence, and correspondence with autobiographical memory. Compared with the non-digital group, patients in the digital group were more willing to share their memories and stories from the past, and they provided positive feedback on the presentation of digital photos and the use of Taiwanese voiceovers. In terms of narrative context, this study identified six main narrative contexts, including contentment, achievement, positivity, social interaction, family affection, and instability. Most patients focused on the "contentment," "family affection," and "achievement" parts. This study can serve as a useful reference for applying digital nostalgia technology to improve the quality of life and mental health of dementia patients, as it provides a deeper understanding of their narrative content and needs.